The Influence of Students' Cultural Diversity on Their Social Interactions in Uganda Christian University Mukono District - Sylivia Nanyondo (Uganda Christian University, 2025)
Locally Uganda Christian University is a private institution which has diverse student body from different cultural backgrounds. According to (Mugny Gabriel; et al, 2010)explored how cultural diversity affects social interactions in many educational institutions in Kampala, they found out that students group themselves according to cultural and regional similarities and this can lead to social divisions and tribalism. The targeted population for the study were all students enrolled at Uganda Christian University who were twenty and lecturers as key informants were five totaling to 25 respondents., the researcher used exploratory research design for the study, this design helped the researcher to explore new phenomenon or area of where little was known, this design also provided a deeper understanding, identified patterns and discovered new insights. The researcher concluded that at least in the context of the Uganda Christian University the majority of the faculty and students recognize their beliefs, biases, values and assumptions about human conduct and how these affect their perception of the students in culturally diverse classrooms, they demonstrate inadequate knowledge of the international students’ values, norms and languages. The researcher recommended that Uganda Christian University should reestablish the culture of appropriate dressing codes that seemed to be on decline may be due to complacency of the policy implementers so as to promote the values of the university as one of the best institutions in Uganda Christian vii University. (Najjengo, 2017)
Undergraduate